The young Leonardo : art and life in fifteenth-century Florence - Feinberg, Larry J. (New York : Cambridge University Press, 2011)
"This book explores Leonardo's origins and the beginning of his career as an artist"--
"Leonardo da Vinci is often presented as the "Transcendent Genius," removed from or ahead of his time. This book, however, attempts to understand him in the context of Renaissance Florence. Larry J. Feinberg explores Leonardo's origins and the beginning of his career as an artist. While celebrating his many artistic achievements, the book illuminates his debt to other artists' works and his struggles to gain and retain patronage, as well as his career and personal difficulties. Feinberg examines the range of Leonardo's interests, including aerodynamics, anatomy, astronomy, botany, geology, hydraulics, optics, and warfare technology, to clarify how the artist's broad intellectual curiosity informed his art. Situating the artist within the political, social, cultural, and artistic context of mid- and late-fifteenth-century Florence, Feinberg shows how this environment influenced Leonardo's artistic output and laid the groundwork for the achievements of his mature works"--
1. Childhood -- 2. Florence and Cosimo the Elder -- 3. The cultural climate of Florence -- 4. First years in Florence and the Verrocchio workshop -- 5. First works in Florence and the artistic milieu -- 6. Early pursuits in engineering: hydraulics and the movement of water -- 7. The Bust of a Warrior and Leonardo's creative method -- 8. Early participation in the Medici court -- 9. Leonardo's personality and place in Florentine society --10. Important productions and collaborations in the Verroccio shop -- 11. Leonardo's colleagues in the workshop --12. Leonardo's Madonna of the Carnation and the exploration of optics -- 13. The Benois Madonna and continued meditations on the theme of sight -- 14. The Madonna of the Cat -- 15. Leonardo, the Medici, and public executions -- 16. Leonardo and Ginevra de'Benci -- 17. Leonardo as portraitist and master of the visual pun -- 18. The young sculptor -- 19. The Madonna Litta -- 20. The Adoration of the Magi and invention of the High Renaissance style -- 21. The Adoration and Leonardo's military interests -- 22. Leonardo and allegorical conceits for the Medici court -- 23. Early ideas for the Last Supper -- 24. Leonardo and the Saint Sebastian -- 25. Saint Jerome -- 26. First thoughts for the Virgin of the Rocks and the invention of the Mary Magdelene-courtesan genre -- 27 Milan -- 28. Leonardo and the Sforza court
Includes bibliographical references (p. 189-200) and index.
Keywords: Leonardo, -- da Vinci, -- 1452-1519.; Artists -- Italy -- Biography; Florence (Italy) -- Civilization; Florence (Italy) -- History -- 1421-1737.